(y-7)-y=6

Simple and best practice solution for (y-7)-y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-7)-y=6 equation:


Simplifying
(y + -7) + -1y = 6

Reorder the terms:
(-7 + y) + -1y = 6

Remove parenthesis around (-7 + y)
-7 + y + -1y = 6

Combine like terms: y + -1y = 0
-7 + 0 = 6
-7 = 6

Solving
-7 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4(v-7)+2v=8 | | 23+3y-2=14y-14-4y | | (3/7)-(x/4)=1/28 | | x-(y-z+2)= | | (2x^2)+16x+22=0 | | 2(x+4)(3x+1)= | | 12+0.25=20.05 | | a+(-b-c)= | | 450-2X+X^2=0 | | 2(x+4)(3x+1)=0 | | 2x^2-8x-120= | | 108x+4=59x-2 | | (2t-4)/(t^2-4) | | 4x-5(4)=20 | | 6x+2=122 | | X^2-30x+207=0 | | (11z-2)(10z+9)=0 | | 24x^2-4x^3=0 | | (X^2+3x)-(x+4)(3x+8)=(3x+8)(x+3) | | (3b-4)-(-5b+3)= | | 2.4/3 | | 5x^2-8x+4=628 | | ln*4+ln*x=ln*7+ln(2x-2) | | 19=17-2x+5x | | 5-2x=3+2x+2 | | 8B+7X=5A | | 7X+8B=5A | | 4x=20+5x | | -1/3m-7=4 | | 0.7+0.05y=0.715 | | x^4-x^3-2x^2= | | 4a+8=11 |

Equations solver categories